2021
DOI: 10.3897/bdj.9.e67449
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton species composition and diversity in the seagrass habitat of Lawas, Sarawak, Malaysia

Abstract: Seagrass habitats are considered to be some of the most biodiverse ecosystems on the planet and safeguard some ecologically and economically important fauna, amongst which are some globally threatened species, including dugong. Malaysian seagrass ecosystems are not widespread, but their existence supports some significant marine fauna. A rigorous zooplankton study was conducted from May 2016 to February 2017, in the seagrass habitat of Lawas, Sarawak, Malaysia, to examine their temporal composition and diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The highest abundance of zooplankton was 346.14 ± 7.22 ind./L, and the lowest was 211.52 ± 11.01 ind./L in the homestead ponds of the study area. A similar abundance of zooplankton was found by [50], which was relatively lower than that of the other studies [41,42,46,47]; this may be due to differences in the ecosystems as well as lack of feeding and fertilization in the studied homestead ponds [38]. The mean abundance of the zooplankton was found to be higher (301.19 ± 40.55 ind./L) in February and lower (293.02 ± 21.12 ind./L) in December in the present study.…”
Section: Zooplankton Abundance and Diversitysupporting
confidence: 81%
See 1 more Smart Citation
“…The highest abundance of zooplankton was 346.14 ± 7.22 ind./L, and the lowest was 211.52 ± 11.01 ind./L in the homestead ponds of the study area. A similar abundance of zooplankton was found by [50], which was relatively lower than that of the other studies [41,42,46,47]; this may be due to differences in the ecosystems as well as lack of feeding and fertilization in the studied homestead ponds [38]. The mean abundance of the zooplankton was found to be higher (301.19 ± 40.55 ind./L) in February and lower (293.02 ± 21.12 ind./L) in December in the present study.…”
Section: Zooplankton Abundance and Diversitysupporting
confidence: 81%
“…Bosmina sp and Mesocyclops sp, indicates a high amount of suspended material in the water body. The zooplankton communities identified from Lakshadweep Archipelago, India (56 species, 7 groups) [41], from a seagrass habitat (45 species, 13 groups) [42] and a man-made lake (27 species, 3 groups) in Malaysia [43], from the maritime channel systems in the Bay of Bengal (32 species, 11 groups) [1], and from a salt marsh estuary, Cox's Bazar (33 species, 11 groups), in Bangladesh [44] were far more numerous than those in the present study, which can be attributed to diversified ecosystems. However, several previous studies have recorded a similar number of zooplankton species in brood ponds (11 genera, 6 groups) [45], Kaptai Lake (10 genera, 3 groups) [46], and aquaculture ponds (9 genera, 4 groups) [47].…”
Section: Zooplankton Communitiesmentioning
confidence: 99%
“…The cluster analysis of fishes revealed two distinct clusters; the closest station to the power plant and SEB4 formed one cluster; whereas, station SEB2 and SEB3 formed another cluster, indicating that the number of fishes in each cluster was nearly identical. Different research groups performed similar cluster analysis, habitats and other groups of the organism (Al-Asif et al, 2020; Johan et al, 2020;Ismail et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The overall seagrass biodiversity in Johor was assessed by Sabri et al [72]. Japar Sidik & Zakaria [73] reported the cause of purple colo- [94]; 12 [95]; 13 [96]; 14 [97]; 15[27]; 16 [4]; 17 [99]; 18[62]; 19 [100]; 20 [28]; 21 [101]; 22 [102]; 23 [61]; 24 [103]; 25 [104]; 26 [105]; 27 [106]; 28 [107]; 29 [30]; 30 [108]; 31 [109]; 32[39]; 33 [110]; 34[63]; 35 [111]; 36 [112]; 37 [113]; 38 [65]; 39 [114]; 40 [115]; 41[59]; 42 [116]; 43 [117]; 44 [118]; 45 [119]; 46[60]; 47 [76]; 48 [123];49 [121]; 50 [122]; 51 [120]; 52 [75]; 53 [58]; 54 [74]; 55 [73]; 56 [72]; 57 [124]; 58 [125]; 59[70]; 60 [126]; 61[51]; 62 [127]; 63 [128]; 64[50]; 65[69]; 66 [18]; 67…”
Section: Biology and Distributionmentioning
confidence: 99%
“…However, the first published documents on seagrass-associated fauna were found in 2004 by Mohammad-Noor et al [41] and the number of publications on this topic has grown over time. Sea cucumbers from Penang island [93,146], zooplankton from Lawas, Sarawak [94], dugong feeding grounds from the Sibu Archipelago, Malaysia [87], and Molluscan communities from Penang, Malaysia [95] were all reported in recent documents. The previously published documents suggested that fauna, for instance, fishes [4,47,48,97,104,106,142,[147][148][149][150], different fish larvae [131,[151][152][153][154][155][156][157][158][159][160] [138,[172][173][174], porcellidiidae [124], crabs [175,176], polychaeta [170], seahorse [111,177], plankton [97,101,132,135,[178][179][180][181], dugong…”
Section: Seagrass-associated Faunamentioning
confidence: 99%